Seemingly irresponsible but welfare improving fiscal policy at the lower bound - Roberto M. Billi; Carl E. Walsh (Sveriges Riksbank, 2022)
In this paper, we evaluate the consequences of super-active fiscal policy rules - that is, rules that call for tax cuts and/or spending increases as the government's debt level rises - in a standard New Keynesian model subject to an occasionally-binding zero lower bound on the monetary policy interest rate. We show that such seemingly irresponsible, debt-financed fiscal stimulus at the ZLB, unbacked by any promise of future tax increases or spending cuts, not only improves economic stability by acting as an automatic stabilizer, but also, somewhat paradoxically, reduces government debt accumulation. When evaluated using a model-consistent measure of welfare, fiscal rules calibrated to the U.S. response during both the Great Recession and COVID recession, combined with a weak monetary policy response to inflation, outperform a monetary policy that responds strongly to inflation and reduce the frequency of episodes at the ZLB.
Keywords: E31; E52; E63; 330; automatic stabilizers; fiscal and monetary interactions; government debt